2019
DOI: 10.3390/cells8080913
|View full text |Cite
|
Sign up to set email alerts
|

IGF2/IGF1R Signaling as a Therapeutic Target in MYB-Positive Adenoid Cystic Carcinomas and Other Fusion Gene-Driven Tumors

Abstract: Chromosome rearrangements resulting in pathogenetically important gene fusions are a common feature of many cancers. They are often potent oncogenic drivers and have key functions in central cellular processes and pathways and encode transcription factors, transcriptional co-regulators, growth factor receptors, tyrosine kinases, and chromatin modifiers. In addition to being useful diagnostic biomarkers, they are also targets for development of new molecularly targeted therapies. Studies in recent decades have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 113 publications
(140 reference statements)
1
26
0
Order By: Relevance
“…A MYB oncogene fusion, through Akt and mitogenactivated protein kinase (MAPK) signaling pathways, activates the expression of NSR, MET, EGFR, IGF1R, and specifically IGF2. The latter, by autocrine stimulation, controls the expression of MYB-NFIB in ACC cells, increasing proliferation and generating changes in the cell cycle and RNA processing (89)(90)(91). Other MYB-related fusions were described, but at lower frequencies than MYB-NFIB.…”
Section: Myb-nfib Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A MYB oncogene fusion, through Akt and mitogenactivated protein kinase (MAPK) signaling pathways, activates the expression of NSR, MET, EGFR, IGF1R, and specifically IGF2. The latter, by autocrine stimulation, controls the expression of MYB-NFIB in ACC cells, increasing proliferation and generating changes in the cell cycle and RNA processing (89)(90)(91). Other MYB-related fusions were described, but at lower frequencies than MYB-NFIB.…”
Section: Myb-nfib Pathwaymentioning
confidence: 99%
“…Other MYB-related fusions were described, but at lower frequencies than MYB-NFIB. Myb overexpression can also occur in the absence of detectable genetic alterations, implying that unknown pathways may be involved in its expression at the protein level (89).…”
Section: Myb-nfib Pathwaymentioning
confidence: 99%
“…Recent studies have shown that this translocation results in a fusion of the transcriptional coactivators MAML2 and CRTC1, and MAML2 and CRTC3. MAML2 belongs to a family of Mastermind‐like, nuclear proteins that function as coactivators for Notch receptors, whereas CRTC1 and CRTC3, CREB‐regulated transcription coactivator 1 and 3, belong to a family of highly conserved CREB, cAMP response element‐binding protein, coactivators . Although the finding of t (11;19)(q21‐22;p13) in WT may indicate malignant transformation, clinical studies have demonstrated that patients with fusion‐positive MECs have a significantly better prognosis compared to those with fusion‐negative tumours, thus establishing CRTC1‐MAML2 as a clinically useful biomarker for MECs .…”
Section: Wt Geneticsmentioning
confidence: 99%
“…Notably, we have previously shown that NFIB which encodes a DNA‐binding transcription factor, is also involved in a gene fusion in salivary gland adenoid cystic carcinomas (ACCs) 23 . The genomic hallmark of these tumors is a t(6;9)(q23;p23) translocation resulting in a MYB‐NFIB gene fusion 23‐25 . The MYB‐NFIB fusion protein consists of the MYB DNA‐binding and transactivation domains fused to the C‐terminal end of NFIB 23 …”
Section: Introductionmentioning
confidence: 99%